PERAN BAZNAS DALAM MENINGKATKAN EKONOMI UMAT: STUDI LITERATUR - Nilal Fauza (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2023)
This article discusses the role of BAZNAS in Indonesia in improving the people's economy. This article is guided by one problem question, namely what is the role of BAZNAS in improving the people's economy? The research method used in this study is an internet-based literature study, namely the Google Scholar database. The types of literature collected in this study are limited to articles in scientific journals, which were published in the 2016-2022 period. The articles that have been downloaded are then entered into the Mandeley software, then imported into the Nvivo software, to be studied and analyzed, resulting in a concluding answer to the research questions posed. The researcher found that the main themes regarding the role of BAZNAS in improving the people's economy are: first, the general role; second, a special role. The special role of BAZNAS includes four sub-themes while the general role of BAZNAS includes three sub-themes. The special roles of BAZNAS are: 1) increasing mustahik capital; 2) encourage economic growth; 3) increasing mustahik's income; and 4) spreading the values of zakat. Meanwhile, in general, BAZNAS plays a role in: 1) fulfilling the right to health; 2) fulfillment of the right to education; 3) provision of social assistance. The contribution of this study is to map previous studies regarding the role of BAZNAS in Indonesia in a broader context, so that it can be followed up in the form of field research, based on recommendations from the results of this study.